A four-questions perspective on public information use in sticklebacks (Gasterosteidae). Issue 2 (20th February 2019) - Webster, Mike M.; Chouinard-Thuly, Laura; Herczeg, Gabor; Kitano, Jun; Riley, Riva; Rogers, Sean; Shapiro, Michael D.; Shikano, Takahito; Laland, Kevin N.
Abstract : Whether learning primarily reflects general processes or species-specific challenges is a long-standing matter of dispute. Here, we present a comprehensive analysis of public information use (PI-use) in sticklebacks (Gasterosteidae). PI-use is a form of social learning by which animals are able to assess the relative quality of resources, here prey patches, by observing the behaviour of others. PI-use was highly specific with only Pungitius and their closest relative Culaea inconstans showing evidence of PI-use. We saw no effects of ontogenetic experience upon PI-use in Pungitius pungitius . Experiments with live demonstrators and animated fish revealed that heightened activity and feeding strikes by foraging conspecifics are important cues in the transmission of PI. Finally, PI-use was the only form of learning in which P. pungitius and another stickleback, Gasterosteus aculeatus differed. PI-use in sticklebacks is species-specific and may represent an 'ecological specialization' for social foraging. Whether this reflects selection on perception, attentional or cognitive processes remains to be determined.